Consider the editor : textual process in the fiction of Raymond Carver and David Foster Wallace - Groenland, Tim (Trinity College (Dublin, Ireland). School of English, 2015)
This thesis examines the contribution of Gordon Lish and Michael Pietsch to key works of Raymond Carver and David Foster Wallace, respectively. The Prologue situates the two authors in a historical framework, considering the reception of their work in the context of the prevalent Minimalist narrative model of 1980s U.S. fiction and the subsequent return to a more expansive, maximal aesthetic. Chapter One then explores the role of the editor from a theoretical and historical perspective, detailing the practical requirements of the editing process and examining the tensions inherent within it. This is followed by the introduction of theoretical perspectives (textual and genetic criticism) that focus on textual process rather than product and whose critical vocabulary is suited to the study of manuscript evidence.
Keywords: English, Ph.D.; Ph.D. Trinity College Dublin.